2017
DOI: 10.1007/s10549-017-4603-z
|View full text |Cite
|
Sign up to set email alerts
|

Late breast cancer treatment-related symptoms and functioning: associations with physical activity adoption and maintenance during a lifestyle intervention for rural survivors

Abstract: Poorer physical functioning was associated with lower PA adoption, and poorer mental and physical functioning was associated with lower maintenance of PA, while late symptoms generally were not. Interventionists should consider level of functioning when identifying individual PA goals during weight management interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Participant and study characteristics are reported in Table 1 . Of the 16 papers, eight were from the United States (US) [ 37 – 44 ], with the remaining from Australia [ 31 , 36 , 45 ], Ireland [ 46 , 47 ], Canada [ 48 ], Pakistan [ 49 ] and Poland [ 50 ]. Participants were mainly recruited through cancer registries ( n = 7) or regional or community cancer centers and hospitals/local clinics ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant and study characteristics are reported in Table 1 . Of the 16 papers, eight were from the United States (US) [ 37 – 44 ], with the remaining from Australia [ 31 , 36 , 45 ], Ireland [ 46 , 47 ], Canada [ 48 ], Pakistan [ 49 ] and Poland [ 50 ]. Participants were mainly recruited through cancer registries ( n = 7) or regional or community cancer centers and hospitals/local clinics ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
“…The number of years since diagnosis was reported in 9 studies (4580 participants), with 27% ≤ 1-year post-diagnosis, 44% between 1 and 5 years, and 30% more than 5. Nine studies (10 papers) were conducted among breast cancer survivors alone [ 31 , 36 , 37 , 39 , 40 , 44 , 47 – 50 ] and comprised 80% of the total participant sample. Eight studies (nine papers) reported rural-only data [ 36 , 37 , 39 43 , 45 , 48 ], and seven studies (seven papers) provided a comparison with an urban population [ 31 , 38 , 44 , 46 , 47 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, one must consider the limitation of wearables in tracking specific types of physical activity 196 (eg, weight training, swimming) or physical activity of frail individuals 171 (eg, walking very slowly), as step count or minutes of walking or running would not suffice. Additionally, in the few studies that demonstrated no significant effect of wearable devices and interventions on increasing physical activity, possible limitations include practical barriers to adherence (eg, technical difficulties, 190 poorer physical functioning, 46 financial barriers 160 ); psychological barriers to adherence (eg, preference for personal vs. automated support, emotional/social/cognitive challenges) 145 , 185 ; and intervention design (eg, duration or intensity of intervention, insufficient statistical power). 65 , 70 , 80 , 103 , 150 , 151 Such findings can be very informative for rehabilitation planning by highlighting the importance of accessible, personal, multimodal intervention programs tailored to the needs of individuals, 10 , 13 , 14 , 28 , 55 particularly in the context of patients with cancer and survivors relative to the healthy population; as well as ongoing support, possibly through peer- or community-support programs.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in this review inform prognostication by examining physical activity levels and its correlates to identify potential patient profiles and their association with various clinical outcomes. These outcomes include physical well-being measures such as anthropometric measures, 31 , 45 , 51 , 63 , 64 , 70 , 82 , 106 , 109 , 113 , 124 , 179 performance status, 26 , 39 , 56 , 62 , 67 , 85 , 120 , 128 motor function, 71 , 92 , 208 functional recovery, 17 , 117 bone health, 162 and symptoms or pain, 12 , 27 , 38 , 39 , 41 , 51 , 56 , 63 , 99 , 126 , 163 quality of life 13-16 , 18 , 24 , 25 , 29 , 32 , 34 , 37 , 39 , 41 , 46 , 47 , 53 , 60 , 67 , 69 , 75 , 80 , 87 , 93 , 101 , 111 , 113 , 114 , …”
Section: Discussionmentioning
confidence: 99%
“…Further, psychological barriers and reduced mental functioning, relating to a cancer diagnosis and treatment, have been described as influencing participants' ability to maintain a healthy diet and physical activity behavior once intervention support ceases. (Fazzino et al, 2018).…”
Section: Study Populationmentioning
confidence: 99%